Implementación de redes neuronales para estimar la resistencia a la compresión del concreto utilizando agregados reciclados y materiales cementales suplementarios (2020)
The implementation of neural networks in the prediction of state properties hardened concrete based on its dosage has been determined as a solution to the high complexity of the problem. This document will implement hidden layer feed-foward neural network architectures to predict resistance 28 days of concrete mixes with recycled aggregates and cementitious materials supplementary from its dosage, water-cement ratios and indices of chemical composition of cementitious materials